2009
DOI: 10.1007/s12289-009-0459-z
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of friction stir welding process

Abstract: Thermo-mechanical simulations of the friction stir butt welding and friction stir spot welding processes were performed for AA5083-H18 sheets, utilizing commercial FVM codes which are based on the Eulerian formulation. For the friction stir butt welding process, the computational fluid dynamics code, STAR-CCM+, was utilized under the steady state condition. Temperature and strain rate histories along the material flow were calculated and simulated temperature distributions (profiles and peak values) were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…[ 9–13 ] Kim et al. [ 14 ] studied the corrosion behavior of pure single crystal Zr with small size in 360 °C and 18.6 MPa condition, and the results showed that the growth rate of oxide film (ZrO 2 ) on the (1 1 2 0) crystal plane was significantly faster than that on the (0 0 0 1) crystal plane. Zhou et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9–13 ] Kim et al. [ 14 ] studied the corrosion behavior of pure single crystal Zr with small size in 360 °C and 18.6 MPa condition, and the results showed that the growth rate of oxide film (ZrO 2 ) on the (1 1 2 0) crystal plane was significantly faster than that on the (0 0 0 1) crystal plane. Zhou et al.…”
Section: Introductionmentioning
confidence: 99%
“…Zirconium alloy was in the form of a hexagonal close-packed (HCP) crystal structure and researchers also have done a lot of studies on its anisotropic corrosion. [9][10][11][12][13] Kim et al [14] studied the corrosion behavior of pure single crystal Zr with small size in 360 °C and 18.6 MPa condition, and the results showed that the growth rate of oxide film (ZrO 2 ) on the (1 1 2 0) crystal plane was significantly faster than that on the (0 0 0 1) crystal plane. Zhou et al [15] found that the growth of oxide film (ZrO 2 ) presented significant anisotropy when the Zr-4 samples with large grains size (≈0.2-0.8 mm) were corroded in 360 °C LiOH aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Dongun Kim et al calculated the temperature distribution and plastic deformation during FSW process, continuity and momentum equation as well as energy equation are solved with temperature dependent or temperature and strain rate dependent material properties. The constitutive law (for the mechanical strain) was assumed [2]. Rosenthal did the most important early work on the theory of the effect of moving sources of heat.…”
Section: Introductionmentioning
confidence: 99%
“…It has been investigated by several authors considering thermal or thermomechanical framework [2][3][4][5][6][7][8]. The difficulty in modeling this welding type resides to large deformations generated by the material mixing.…”
Section: Introductionmentioning
confidence: 99%